H α emission in the nebular spectrum of the Type Ia supernova ASASSN-18tb. Issue 3 (3rd April 2019) - Kollmeier, Juna A; Chen, Ping; Dong, Subo; Morrell, Nidia; Phillips, M M; Kushnir, Doron; Prieto, J L; Piro, Anthony L; Simon, Joshua D
ABSTRACT: As part of the 100IAS survey, a program aimed to obtain nebular-phase spectra for a volume-limited and homogeneous sample of Type Ia supernovae (SNe Ia), we observed ASASSN-18tb (SN 2018fhw) at 139 d past maximum light. ASASSN-18tb was a fast-declining, sub-luminous event that fits well within the observed photometric and spectroscopic distributions of the SN Ia population. We detect a prominent H α emission line ( L H α  = 2.2 ± 0.2 × 10 38  ergs s −1 ) with FWHM ≈ 1100 km s −1 in the nebular-phase spectrum of this SN Ia. High-luminosity H α emission ( L H α ≳ 10 40  ergs s −1 ) has previously been discovered in a rare class of SNe Ia-like objects showing circum-stellar medium (CSM) interactions (SNe Ia–CSM). They predominantly belong to overluminous ( M max < −19 mag in optical) 1991T-like SNe Ia and are exclusively found in star-forming galaxies. By contrast, ASASSN-18tb is a sub-luminous SN Ia ( M B, max ∼ −17.7 mag) found in an early-type galaxy dominated by old stellar populations. We discuss possible origins for the observed hydrogen. Of the 75 SNe Ia for which we have so far obtained nebular spectra in 100IAS, no other SN shows a ${\sim } 1000 \, {\rm km\, s^{-1}}$ H α emission line with comparable line luminosity as ASASSN-18tb, emphasizing the rarity of such emission in the nebular phase. Based on preliminary results from our survey, the rate for ASASSN-18tb-like nebular H α emission could be as high as ${\sim } 10{{\ \rm per\ cent}}$ among sub-luminous SNe Ia.